The Role of Village-Owned Enterprises (Bumdes) in Achieving a Green Economy through Waste Banks in Transforming Waste to Diesel Energy - Santoso, Bagus Teguh; Ismail, Ismail; Azizah, Anisa Kurniatul; Adha, Fajar (Universitas Muhammadiyah Tangerang, 2024)
In the effort to manage waste, waste processing is frequently handled by larger groups or stakeholders with substantial capital. Therefore, this scholarly work proposes the independent processing of waste using financially accessible equipment. This initiative is grounded in waste mitigation efforts commencing early at the village governance level, acting as collectors and managers of waste. This concept aligns with the elevation of economy based on green economics, considering the global Sustainable Development Goals (SDGs) program. The implementation of this concept yields a dual impact, strengthening the village economy through BUMDES while simultaneously mitigating environmental pollution resulting from poorly managed waste. This research utilizes a normative method with statutory, conceptual, and field approaches. This study is tested in Balun Village, Turi Sub-district, Lamongan Regency, East Java Province, through collaboration between the Village-Owned Enterprise